Some new trends in the design of single molecule magnets - Aldoshin, Sergey M.; Korchagin, Denis V.; Palii, Andrew V.; Tsukerblat, Boris S. (Pure and applied chemistry, 2017)
In this review we briefly discuss some new trends in the design of single molecule magnets based on transition (3d, 4d, 5d) and rare-earth (4f) metal ions. Within this broad theme the emphasis of the present review is placed on the molecules which exhibit strong magnetic anisotropy originating from the unquenched orbital angular momenta in the ground orbitally degenerate (or quasi-degenerate) states. Along with the general concepts we consider selected examples of the systems comprising orbitally-degenerate metal ions and demonstrate how one can benefit from strong single-ion anisotropy arising from the first-order orbital angular momentum. The role of crystal fields, spin-orbit coupling and structural factors is discussed. Some observation stemming from the analysis of the isotropic exchange interactions, magnetic anisotropy and strongly anisotropic orbitally-dependent superexchange are summarized as guiding rules for the controlled design of single molecule magnets exhibiting high barriers for magnetization reversal and, consequently, high blocking temperatures.